Deep Sea Sediment Gravity Flow Deposits in Gulf of Tomini, Sulawesi - Kusnida, Dida; Subarsyah, Subarsyah (Geological Agency, 2008)
http://dx.doi.org/10.17014/ijog.vol3no4.20084Micro plate collision against the Eastern Arm of Sulawesi since Pliocene has resulted in a major supply of terigenous sediments into Late Miocene rift-basins in Gulf of Tomini. Studies on offshore multi-channel seismic reflection data complemented by published on-land geological data indicate a series of tectonic events that influenced the depositional system in the Gulf of Tomini. During the Late Neogene, alternating pulses of terigenous sediments were deposited in the basins in the form of deep-sea slump-turbidite-pelagic sediments. A sediment gravity flow deposit system at the slope and the base of the basins changed gradually into a deep-sea pelagic fill system toward the center of the basins. Three tectono-stratigraphy sequences (A, B, and C) separated by unconformities indicating the Late Neogene history and the development of the basins were identified. These tectonic processes imply that the earlier sediments in the Gulf of Tomini are accomplished by a differential subsidence, which allows a thickening of basin infill. The Pliocene-Quaternary basin fill marks the onset of a predominant gravity flow depositional system Â